Assessing the Effects of Court Date Notifications within Pretrial Case Processing - Lowenkamp, Christopher T. (American journal of criminal justice, 2018)
Jurisdictions at every level throughout the U.S. are paying an increasing amount of attention to pretrial case processing. The primary areas of attention appear to be on risk assessment development and classification, the effects of pretrial detention, and the effectiveness of various strategies that may impact a defendant’s failure to appear for their assigned court dates. The current study is a randomized experimental trial designed to test the effects of court notification strategies, using failure to appear (FTA) as the primary outcome of interest. Our findings do not reveal a palpable effect for court notification strategies (telephone calls, and text messaging, with other conditions layered in), but do indicate and reinforce the utility of an actuarial method of risk classification when predicting likelihood of FTA.